New chaotic encryption algorithm based on chaotic sequence and plain text. Issue 3 (1st May 2014) - Wang, Xing‐Yuan; Gu, Sheng‐Xian
Abstract : A new chaotic encryption algorithm is proposed. Its key is based on chaotic sequence and plain text. First, the chaotic sequence and the plain text are used; the result is the key, so even someone obtains the initial value he cannot decrypt the cipher text. The initial value is destroyed. Then the key is used to encrypt the plain text and destroy the plain text. If someone obtains the chaotic initial value, he still cannot decrypt the cipher text because the real key is based on chaotic sequence and plain text. Obviously the other people do not have the plain text. So, the key cannot be obtained by others. The other people have to use force‐to‐attack way to decrypt the cipher text. From the result of the experiments, one can see that the algorithm's security is improved and strengthened.